Analisis Optimasi Parameter Permesinan Terhadap Kebulatan Benda Kerja Pada Mesin CNC Turning SL-25 Mori Seiki dengan Metode Taguchi - Oktavia, Davina; Oktriadi, Yudi; Mayang Sari, Elisa (Jurnal Inovasi Teknologi Terapan, 2024)
In handle machining, generation is something that must be prioritized. Roundness is one of the geometric shapes that's taken under consideration within the comes about of the turning generation handle. The right utilize of machining parameters in arrange to make strides common quality is anticipated to optimize the comes about of the machining prepare. A few controlled parameters are carried out that are the axle speed, bolster speed and cutting profundity with three levels within the turning handle of ST-60 steel fabric. At that point the roundness of the turning comes about was measured and a fluctuation investigation of the flag to clamor proportion was carried out in agreement with Taguchi's proposed plan. Comes about of change examination of the S/N proportion result that the parameters of bolster speed and nourish profundity are the same essentially with commitment levels of 17,85% and 76,46% impact roundness. Shaft revolution at parameter conditions 2.441 [m/min], bolster speed 0.15 [mm/rev], and a cutting profundity of 1 [mm] are the ideal parameters gotten